Meningkatkan Kemampuan Motorik Kasar Anak Kelompok B Melalui Bermain Estafet di TK Melati Indah Tenanyan Raya - Melvi Lesmana Alim; Vigi Indah Permatha Sari (Jurnal Pendidikan Tuntas, 2024)
This research is based on the low gross motor skills of Group B children at Melati Indah Kindergarten, Tenanyan Raya, then by considering the identification and analysis of problems, the researcher determines an alternative problem solving in the form of applying Estafet Play activities at Melati Indah Kindergarten, Tenanyan Raya to Improve Children's Gross Motor Skills.This research is a collaborative classroom action research. This research was conducted in two cycles with each cycle of two meetings. The subjects in the study were Group B consisting of 11 boys and 15 girls. The methods used to collect data are observation and documentation. The data analysis used is descriptive qualitative and quantitative. The results of this study indicate that through playing relay gross motor skills have increased. This can be seen in the aspect of the speed of children who score 3 (three), namely children who can run quickly and carry out the teacher's instructions correctly in pre-action reached 23.08%, in Cycle I it was 53.85%, and in Cycle II it rose to 88.46%. The aspect of children's agility that scored 3 (three) where children looked agile and could carry out according to the teacher's instructions at pre-action reached 7.69%, in Cycle I it was 42.31%, and in Cycle II it rose to 84.62%. The aspect of eye and hand coordination of children who get a score of 3 (three), namely children who can run according to the teacher's instructions and are able to coordinate their eyes and hands in pre-action reached 19.23%, Cycle I amounted to 46.15%, and in Cycle II increased to 88.64%. Thus, it can be concluded that playing relay can improve the gross motor skills of Group B children at Melati Indah Kindergarten, Tenanyan Raya. Keywords: gross motor skills, relay play, classroom action research